Annemarie Jordan Gschwend and K.J.P. Lowe: The Global City: On the Streets of Renaissance Lisbon - Cherniavsky, Mark (Petits Propos Culinaires, 2016)
Annemarie Jordan Gschwend and K.J.P. Lowe: The Global City: On the Streets of Renaissance Lisbon: Paul Holberton Publishing, 2015: 296 pp., hardback, £40.